THE RELATIONSHIP BETWEEN SMARTPHONE ADDICTION AND ACADEMIC ACHIEVEMENT AMONG ADOLESCENTS: A LITERATURE REVIEW - Wahyudi; Dian Permana; Masruri; Ratri Diana (NATARASA: Journal of Counseling and Psychology, 2026)
The increasing use of smartphones among adolescents has transformed learning patterns, communication, and access to information. While smartphones provide significant educational and social benefits, excessive and uncontrolled use has become a growing concern due to its potential impact on students' academic achievement. This study aims to synthesize and analyze empirical evidence regarding the relationship between smartphone addiction and academic achievement among adolescents. The study employed a literature review method by examining peer-reviewed journal articles published between 2019 and 2025 from reputable databases, including Scopus, Web of Science, ScienceDirect, SpringerLink, Taylor & Francis, and Google Scholar. The selected literature was analyzed using a thematic synthesis approach to identify recurring findings, influencing factors, and research gaps. The review indicates that smartphone addiction is consistently associated with lower academic achievement through various mechanisms, including reduced learning concentration, poor time management, sleep disturbances, academic procrastination, decreased motivation, and excessive engagement with social media and online gaming. Nevertheless, several studies reveal that smartphones can positively support academic performance when used appropriately for educational purposes, collaborative learning, and information retrieval. The findings also highlight that parental supervision, digital literacy, self-regulation, and effective school policies play significant roles in minimizing the negative effects of smartphone addiction. This literature review concludes that the relationship between smartphone addiction and academic achievement is influenced not only by the duration of smartphone use but also by the purpose, intensity, and quality of digital engagement. Therefore, comprehensive interventions involving families, schools, and policymakers are essential to promote responsible smartphone use while enhancing adolescents' academic success and psychological well-being.